MELATONIN SUPPLEMENTATION IN MULTIPLESCLEROSIS: A SYSTEMATIC REVIEW - Muvida; Yunandia Rahmawati; Helen Anince Heretringgi (Magna Neurologica, 2026)
Background: Multiple sclerosis (MS) is a chronic neurodegenerative disease marked by progressive inflammation and demyelination, in which symptom management remains challenging. Melatonin has potential antioxidant and anti-inflammatory effects, but evidence of its efficacy in MS is limited. Objective: This systematic review evaluated the effects of melatonin supplementation on inflammatory biomarkers and symptom-related outcomes in patients with MS using randomized controlled trials (RCTs). Methods: This systematic review was conducted on November 10, 2025, using PubMed, Scopus, and ScienceDirect, including English-language RCTs published within the past ten years. Study quality was assessed using the Cochrane Risk of Bias 2 tool, and the review followed PRISMA guidelines with PROSPERO registration (CRD420251273486). Results: A total of 12 RCTs involving 406 participants were included. Inflammatory biomarkers demonstrated heterogeneous responses, particularly for TNF-α and IFN-1β, with no significant changes observed in C-reactive protein (CRP), whereas oxidative stress biomarkers showed more consistent improvement. Regarding clinical outcomes, melatonin supplementation was associated with improvements in certain symptoms, including pain and fatigue, although findings varied across studies. Cognitive performance particularly executive function, information processing speed, and visuospatial memory showed relatively consistent improvement, while no significant changes were observed in global neurological disability or overall quality of life. Conclusion: Melatonin supplementation in patients with MS demonstrates consistent benefits in reducing oxidative stress and provides limited improvement in symptoms such as pain, fatigue, and cognitive function; however, it does not confer significant benefits on global disability or overall quality of life.